Ecotoxicological evalution of tuberculostatic medicines: Predicted Environmental Concentration and biological effects in Daphnia similis and Echinometra lucunter. (Research, Society and Development, 2021)
The increase in the production of pharmaceutical products has been gradually increasing and, consequently, the residues of these products inappropriately in the aquatic environment as well. In this context, the scarcity of ecotoxicological studies on drugs of the tuberculostatic class in the aquatic environment is highlighted. Thus, the present study aimed to evaluate the presence of tuberculostatic drugs used as a standardized scheme by the Brazilian Ministry of Health for the treatment of tuberculosis (Rifampicin, Isoniazid, Pyrazinamide and Etambutol), by calculating the predicted environmental concentration (PEC) in surface waters of the municipality from Cubatão (São Paulo, Brazil). In addition, adverse biological effects on the test organisms Daphnia similis and Echinometra lucunter for the drugs Isoniazid and Pyrazinamide were evaluated. The PEC values were calculated among the four tuberculostatic drugs according to the guideline of the European Medicines Agency (EMEA) (CHMP, 2006). Afterwards, toxicity tests were performed on D. similis and E. lucunter according to Brazilian Association of Technical Standards ABNT NBR 12713:2016 e ABNT NBR 15350:2012, respectively. PEC values for all four tuberculostatic drugs included in the present study showed values that exceeded the limit considered by the EMEA of 0.01 µg.L-1. For the toxicity test with D. similis, the drugs Isoniazid and Pyrazinamide presented EC50 values of 69.97 mg.L-1 and 44.49 mg.L-1, respectively, being classified as “harmful” according to the Directive of the European Economic Community (EEC) 93/67 / EEC. As for the toxicity test with E. lucunter, the drugs Isoniazid and Pyrazinamide showed IC50 values of 23.66 mg.L-1 and 17.21 mg.L-1, respectively, results that are also considered “harmful” according to with Directive 93/67 / EEC. The results of this research may serve as subsidies to new legislation and the creation of government programs that seek solutions promoting reduction and even the elimination of pharmaceuticals in the aquatic environment.